3m-6=48

Simple and best practice solution for 3m-6=48 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3m-6=48 equation:


Simplifying
3m + -6 = 48

Reorder the terms:
-6 + 3m = 48

Solving
-6 + 3m = 48

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '6' to each side of the equation.
-6 + 6 + 3m = 48 + 6

Combine like terms: -6 + 6 = 0
0 + 3m = 48 + 6
3m = 48 + 6

Combine like terms: 48 + 6 = 54
3m = 54

Divide each side by '3'.
m = 18

Simplifying
m = 18

See similar equations:

| 3m+6=0 | | -14=y-12 | | 5Y-25X=10 | | 5(4z-1)-3(z+7)=14(z+1) | | 7x+5y=4 | | 12x^2+63x+15=0 | | 0.5x^2+5=14 | | Y^2+10y-56=0 | | 4x^2-9=17 | | 4xy+24x-2x= | | x^2+3-5=0 | | 8x+17=2x+101 | | 6x^2+15=23 | | C^2+15=0 | | 70-4x=32x+22 | | x^2-3x+3=-3 | | 5z=3(z+7) | | 2[3x+5]=170 | | 5x=2y-11 | | x^2-3x+3=3 | | x^2-12=4 | | 3x+3y-bx-by= | | 51*5= | | 6[4x+7]=282 | | -4w^2+w-60=0 | | 0.04x+0.08(20-x)=1 | | 3x(x-5)=5x^2-16x | | 7[x+2]=126 | | =9 | | 10x^3-x^2+1=0 | | 0.04+0.08(20-x)=1 | | (3b^3+5b^2-1)+(2b^3-5b+6)= |

Equations solver categories